A composite electrode of a supported core-shell structure catalyst based on electrochemical dealloying and a preparation method thereof
Patent Information
- Application Number
- CN202611219747.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对现有碳毡电极催化活性不足以及核壳结构催化剂难以在碳毡表面有效负载的问题,本发明提供一种基于电化学脱合金化的负载核壳结构催化剂的复合电极及其制备方法
1、将两次“沉积-脱合金”过程相结合,在碳毡表面原位形成“富导电性组分核心+富催化活性组分壳层”的核壳结构,解决了核壳催化剂在三维基底上难以均匀负载和牢固结合的问题。
Smart Images

Figure CN123017993A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flow battery electrode material technology, specifically a composite electrode based on electrochemical dealloying supported core-shell structure catalyst and its preparation method. Background Technology
[0002] Flow batteries have broad application prospects in large-scale energy storage due to their advantages such as high safety, long life and independent design of power and capacity. However, their performance is generally limited by the insufficient intrinsic catalytic activity of commonly used carbon felt electrodes for key redox reactions. Surface modification is urgently needed to improve the catalytic efficiency and stability of the electrodes in order to promote the further development of this technology.
[0003] Core-shell catalysts have attracted widespread attention in the field of catalysis due to their unique structural advantages. By rationally designing the composition and structure of the core and shell, multiple functions can be achieved synergistically: the core layer provides good electrical conductivity and mechanical support, while the shell layer provides high catalytic activity. However, traditional core-shell catalyst preparation methods, such as seed growth and template methods, often struggle to achieve uniform loading and robust bonding on the three-dimensional carbon felt surface. Summary of the Invention
[0004] To address the issues of insufficient catalytic activity in existing carbon felt electrodes and the difficulty in effectively loading core-shell catalysts onto the carbon felt surface, this invention provides a composite electrode based on electrochemical dealloying and a method for preparing the same. This method involves stepwise electrochemical dealloying, first constructing a porous metal core layer on the carbon fiber surface, and then constructing a porous catalytically active shell layer on its surface, thereby constructing a core-shell porous catalyst layer with a "conductively rich core + catalytically active shell" structure in situ on the carbon fiber surface.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying includes the following: The carbon felt substrate is first acid-treated to introduce oxygen-containing functional groups, and then a first alloy layer is deposited on its surface. The first alloy layer has a first catalytically active component and a first sacrificial component. Then, a first dealloying treatment is performed to remove the first sacrificial component, forming a porous metal core layer with high conductivity. A second alloy layer is then deposited on the porous metal core layer. The second alloy layer has a second catalytically active component and a second sacrificial component. Then, a second dealloying treatment is performed to remove the second sacrificial component, forming a porous shell layer with high catalytic activity. Thus, a core-shell porous catalyst layer is formed in situ on the surface of the carbon felt substrate, resulting in a composite electrode with a core-shell porous catalyst layer loaded on its surface.
[0006] Carbon felt substrates include polyacrylonitrile-based carbon felt, pitch-based graphite felt, adhesive-based carbon felt, or carbon paper.
[0007] The acid treatment includes the following steps: the carbon felt substrate is ultrasonically degreased in acetone, ethanol, and deionized water for 10-30 minutes in sequence, then immersed in 5wt%-30wt% HNO3 or H2SO4 solution at 60℃-90℃ for 1-6 hours to introduce oxygen-containing functional groups, then washed with deionized water until neutral, and then dried at 60℃-100℃ for 6-12 hours.
[0008] The first catalytic active component is selected from one or more of Ni, Co, and Cu; the first sacrificial component is selected from one or more of Zn, Al, and Mg; in the first alloy layer, the total atomic percentage of the first catalytic active component is 30% to 80%, and the total atomic percentage of the first sacrificial component is 20% to 70%.
[0009] The deposition of the first alloy layer includes the following: depositing the first alloy layer on the surface of a carbon felt substrate using an electrochemical deposition method. The electrolyte for electrochemical deposition contains a metal ion salt solution of a first catalytically active component and a first sacrificial component, with a total metal ion concentration of 0.01 mol / L to 0.5 mol / L, a deposition potential of -1.5 V to -0.5 V vs. SCE (relative to a saturated calomel electrode), a deposition time of 5 to 60 minutes, and a deposition temperature of 25°C to 50°C.
[0010] The first dealloying treatment includes the following: selectively dissolving the first sacrificial component in an acidic medium using an electrochemical dealloying method. The acidic corrosive medium is a 0.1 mol / L to 2.0 mol / L H2SO4, HCl, or HNO3 solution. The dealloying potential is -0.2 V to 0.5 V vs. SCE, and the treatment time is 10 to 120 minutes.
[0011] By adjusting the conditions of the first dealloying treatment, the pore size of the porous metal core layer is controlled to be 10nm~100nm, the porosity to be 30%~70%, and the thickness to be 0.5μm~5μm.
[0012] The second catalytic active component is selected from one or more of Pt, Pd, Ir, Ru, Bi, In, and Sb; the second sacrificial component is selected from one or more of Zn, Al, and Mg; in the second alloy layer, the total atomic percentage of the second catalytic active component is 30% to 80%, and the total atomic percentage of the second sacrificial component is 20% to 70%.
[0013] The deposition of the second alloy layer includes the following: depositing the second alloy layer on the porous metal core layer using an electrochemical deposition method. The electrolyte for electrochemical deposition contains a metal ion salt solution of the second catalytically active component and the second sacrificial component. The total metal ion concentration is 0.001 mol / L to 0.1 mol / L, the deposition potential is -1.0 V to -0.4 V vs. SCE, the deposition time is 5 to 30 minutes, and the deposition temperature is 25℃ to 40℃.
[0014] The second dealloying treatment includes the following: selectively dissolving the second sacrificial component in an acidic medium using an electrochemical dealloying method. The acidic corrosive medium is a 0.1 mol / L to 2.0 mol / L H2SO4, HCl, or HNO3 solution. The dealloying potential is -0.2 V to 0.5 V vs. SCE, and the treatment time is 10 to 90 minutes.
[0015] By adjusting the conditions of the second dealloying process, the pore size of the porous shell is controlled to be 5nm~50nm, the porosity to be 30%~60%, and the thickness to be 0.1μm~2μm.
[0016] During the first and second dealloying processes, inert gas is introduced for stirring or ultrasonic assistance, with a gas flow rate of 10 mL / min to 100 mL / min and an ultrasonic power of 50 W to 300 W.
[0017] After the second dealloying treatment, the electrode is rinsed repeatedly with deionized water or ethanol 3 to 5 times and dried in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours to obtain a composite electrode with a core-shell structured porous catalyst layer on its surface.
[0018] The composite electrode prepared by the above method with a supported core-shell porous catalyst layer can be used as a flow battery electrode and is suitable for all vanadium redox flow batteries, iron-chromium redox flow batteries, all iron redox flow batteries and zinc-based redox flow batteries. The catalytically active component of the porous metal core layer contains one or more of Ni, Co, and Cu, and the catalytically active component of the porous shell layer contains one or more of Pt, Pd, Ir, Ru, Bi, In, and Sb. The porous metal core layer has a pore size of 10nm~100nm, a porosity of 30%~70%, and a thickness of 0.5μm~5μm; the porous shell layer has a pore size of 5nm~50nm, a porosity of 30%~60%, and a thickness of 0.1μm~2μm. The specific surface area of the core-shell porous catalyst layer is 15 m². 2 / g~60m 2 / g, with an electrochemical active area of 80mF / cm² 2 ~150mF / cm 2The thickness ratio of the core layer to the shell layer is 1:1 to 10:1, and the aperture ratio of the core layer to the shell layer is 1:1 to 3:1.
[0019] The design concept of this invention is: This invention creatively applies a stepwise electrochemical dealloying method to the modification of flow battery electrodes. Electrochemical deposition combined with dealloying technology provides a new approach for constructing core-shell structures on three-dimensional substrates. Through two stepwise deposition-dealloying processes and selective dissolution, a porous core layer and a porous shell layer are sequentially constructed in situ on the carbon fiber surface. Electron synergistic effects may also occur at the core-shell interface, further enhancing catalytic performance and forming a core-shell porous catalyst layer with a "conductive component-rich core + catalytically active component-rich shell" structure, exhibiting good interfacial bonding and controllable structure.
[0020] First, highly conductive metals such as Ni, Co, and Cu are selected as the first catalytic active components, forming a first alloy layer with sacrificial components such as Zn, Al, and Mg. After the first dealloying, the sacrificial components are selectively dissolved, forming a porous metal core layer with three-dimensional interconnected channels. This core layer has good conductivity, serving as a fast electron transport channel, while its porous structure provides a high specific surface area substrate for subsequent shell deposition.
[0021] Then, noble metals such as Pt, Pd, Ir, and Ru, or metals with excellent catalytic activity against the vanadium redox couple such as Bi, In, and Sb, are selected as the second catalytically active component, forming a second alloy layer with the sacrificial component and deposited on the surface of the porous core layer. After the second dealloying, a porous catalytically active shell layer is formed. This shell layer has abundant catalytically active sites, and its porous structure is conducive to electrolyte penetration and mass transfer.
[0022] This core-shell structure design has the following unique advantages: First, the core layer and shell layer form a good interface bond through stepwise deposition and dealloying, avoiding delamination; second, the high conductivity of the core layer ensures rapid electron conduction, and the high catalytic activity of the shell layer ensures efficient catalysis, with both synergistically improving electrode performance; third, electronic effects may occur at the core-shell interface, further optimizing catalytic activity; and fourth, by adjusting the conditions of the two deposition and dealloying processes, the pore size, thickness, and composition of the core layer and shell layer can be independently controlled, achieving precise regulation of structural performance.
[0023] The advantages and beneficial effects of this invention are as follows: 1. By combining two “deposition-dealloying” processes, a core-shell structure of “conductively rich core + catalytically active shell” is formed in situ on the carbon felt surface, which solves the problem of uniform loading and firm bonding of core-shell catalysts on a three-dimensional substrate.
[0024] 2. By selecting different metal combinations and adjusting deposition parameters, the composition, pore size, and thickness of the core layer (Ni, Co, Cu) and shell layer (Pt, Pd, Bi, In, etc.) can be independently controlled to achieve optimized performance design.
[0025] 3. The core layer provides high conductivity to ensure rapid electron transport, while the shell layer provides high catalytic activity to ensure efficient catalysis. The synergistic effect of the two reduces the charge transfer resistance by 50% to 70% compared to the original electrode.
[0026] 4. The precious metals in the shell are only distributed on the surface and can be maximized through the porous structure, reducing the amount of precious metals used by 50% to 80% compared with the traditional uniform covering method.
[0027] 5. This method is applicable to a variety of metal combinations, and suitable core and shell materials can be selected according to the needs of different flow battery systems. Attached Figure Description
[0028] Figure 1 This is a scanning electron microscope image of the porous catalyst layer of the Ni@Pt core-shell composite electrode prepared in Example 1. Detailed Implementation
[0029] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. It should be noted that the embodiments described in this invention are only for further explanation and illustration, and not for limiting their application scope. Based on this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.
[0030] This invention relates to a method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying, comprising the following steps and process: In the specific implementation process, the carbon felt substrate is first pretreated to introduce oxygen-containing functional groups; then, a porous metal core layer is constructed through a first electrochemical deposition and dealloying; subsequently, a porous catalytically active shell layer is constructed through a second electrochemical deposition and dealloying; finally, the composite electrode is obtained after cleaning and drying. Specifically, the process includes the following: (1) Substrate pretreatment: The carbon felt is cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then, it is immersed in 5wt%~30wt% HNO3 solution at 60℃~90℃ for 1~6 hours to introduce oxygen-containing functional groups and enhance the bonding force between the subsequent alloy layer and the carbon fiber. Then, it is repeatedly rinsed with deionized water until neutral and dried in a vacuum drying oven at 60℃~100℃ for 6~12 hours for later use.
[0031] (2) Construction of porous metal core layer: A porous metal core layer was constructed on the surface of the pretreated carbon felt substrate using electrochemical deposition. An electrolyte containing the first catalytically active component and the first sacrificial component was prepared, and a complexing agent was added. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, the first electrochemical deposition was performed at a constant potential. The total concentration of metal ions was 0.01 mol / L ~ 0.5 mol / L, the deposition potential was -1.5 V ~ -0.5 V vs. SCE, the deposition time was 5 ~ 60 minutes, and the deposition temperature was 25℃ ~ 50℃. After deposition, the substrate was removed, rinsed with deionized water, and dried at room temperature.
[0032] The carbon felt coated with the first alloy layer is then placed in an acidic corrosive medium for a first dealloying treatment using a constant potential method. The acidic corrosive medium is a 0.1 mol / L to 2.0 mol / L solution of H₂SO₄, HCl, or HNO₃. The dealloying potential is -0.2 V to 0.5 V vs. SCE, and the treatment time is 10 to 120 minutes. This selectively dissolves the first sacrificial component, forming a porous metal core layer with a pore size of 10 nm to 100 nm, a porosity of 30% to 70%, and a thickness of 0.5 μm to 5 μm.
[0033] (3) Construction of a porous catalytically active shell: A highly catalytically active porous shell was constructed on the surface of a porous metal core layer using an electrochemical deposition method. An electrolyte containing a second catalytically active component and a second sacrificial component was prepared, and a complexing agent was added. A carbon felt coated with a porous metal core layer was used as the working electrode, and a second electrochemical deposition was performed at a constant potential. The total concentration of metal ions was 0.001 mol / L to 0.1 mol / L, the deposition potential was -1.0 V to -0.4 V vs. SCE, the deposition time was 5 to 30 minutes, and the deposition temperature was 25℃ to 40℃. After deposition, the shell was removed, rinsed with deionized water, and dried at room temperature.
[0034] The carbon felt coated with the second alloy layer is then placed in an acidic corrosive medium for a second dealloying treatment using a potentiostatic method. The acidic corrosive medium is a 0.1 mol / L to 2.0 mol / L solution of H₂SO₄, HCl, or HNO₃. The dealloying potential is -0.2 V to 0.5 V vs. SCE, and the treatment time is 10 to 90 minutes. This selectively dissolves the second sacrificial component, forming a porous catalytically active shell with a pore size of 5 nm to 50 nm, a porosity of 30% to 60%, and a thickness of 0.1 μm to 2 μm.
[0035] (4) Post-treatment: The electrode after the second dealloying treatment is rinsed repeatedly with deionized water 3 to 5 times and dried in a vacuum drying oven at 60℃ to 100℃ for 6 to 12 hours to obtain a modified carbon felt composite electrode with a core-shell structured porous catalyst supported on the surface.
[0036] The raw materials and equipment used, such as carbon felt of different specifications and metal salts, are all commercially available.
[0037] The present invention will now be described in further detail through embodiments.
[0038] Example 1 Fabrication of Ni@Pt core-shell structured porous composite electrode (Ni core + Pt shell).
[0039] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0040] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0041] (3) Construction of porous Pt shell: Preparation of Pt-containing 4+ and Zn 2+ The electrolyte, Pt 4+ The concentration is 0.005 mol / L, Zn 2+ The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.6 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a second Pt-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pt shell.
[0042] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Pt-1.
[0043] Modified carbon felt composite electrode CF-Ni@Pt-1: Scanning electron microscopy as shown Figure 1 As shown, a porous Ni core layer uniformly covers the carbon fiber surface, forming a core-shell structure after the deposition of a Pt shell. Transmission electron microscopy elemental line scanning reveals a clear distribution of the Ni core and Pt shell, increasing the specific surface area to 28.5 μm². 2 / g, the electrochemical active area increased to 125.6mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 87.5% when tested at current density.
[0044] Example 2 Fabrication of a Co@Pd core-shell porous composite electrode (Co core + Pd shell).
[0045] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0046] (2) Construction of porous Co core layer: Prepare a Co-containing core layer 2+ and Zn 2+ electrolyte, Co 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.15 mol / L, the total concentration was 0.25 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 35 minutes at -1.1 V vs. SCE potential at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Co-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution and subjected to a dealloying treatment at 0.1 V vs. SCE potential for 60 minutes using a potentiostatic method to selectively dissolve Zn, forming a porous Co core layer.
[0047] (3) Construction of porous Pd shell: Prepare a Pd-containing 2+ and Zn 2+ The electrolyte, Pd 2+ The concentration is 0.004 mol / L, Zn 2+The concentration was 0.006 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Co core layer was used as the working electrode, and deposition was performed for 20 minutes at -0.7 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a second Pd-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pd shell.
[0048] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60℃ for 6 hours to obtain the modified carbon felt composite electrode CF-Co@Pd-2.
[0049] Modified carbon felt composite electrode CF-Co@Pd-2: Scanning electron microscopy shows a porous Co core layer uniformly covering the carbon fiber surface, forming a core-shell structure after Pd shell deposition. Transmission electron microscopy elemental line scanning reveals a clear distribution of the Co core and Pd shell, increasing the specific surface area to 26.8 μm². 2 / g, the electrochemical active area increased to 118.3mF / cm 2 Assembled into a single vanadium redox flow battery, achieving a current of 200 mA / cm². 2 The energy efficiency was 86.8% when tested at current density.
[0050] Example 3 Fabrication of Cu@Ir core-shell porous composite electrode (Cu core + Ir shell).
[0051] (1) Substrate pretreatment: The polyacrylonitrile-based carbon felt was cut into 10cm x 10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0052] (2) Construction of porous Cu core layer: Prepare Cu-containing 2+ and Zn 2+ The electrolyte, Cu 2+ The concentration is 0.08 mol / L, Zn 2+The concentration was 0.12 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L potassium sodium tartrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 25 minutes at -0.9 V vs. SCE potential at a deposition temperature of 30℃. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Cu-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 50 minutes, selectively dissolving Zn to form a porous Cu core layer.
[0053] (3) Construction of porous Ir shell: preparation of Ir 3+ and Zn 2+ electrolyte, Ir 3+ The concentration is 0.003 mol / L, Zn 2+ The concentration was 0.007 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Cu core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.8 V vs. SCE potential at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with an Ir-Zn second alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.2 V vs. SCE potential for 30 minutes, selectively dissolving Zn to form a porous Ir shell.
[0054] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Cu@Ir-3.
[0055] Modified carbon felt composite electrode CF-Cu@Ir-3: Scanning electron microscopy reveals a porous Cu core layer uniformly covering the carbon fiber surface, forming a core-shell structure after the deposition of an Ir shell. Transmission electron microscopy elemental line scanning shows a clear distribution of the Cu core and Ir shell, increasing the specific surface area to 24.5 μm². 2 / g, the electrochemical active area increased to 112.5mF / cm 2 Assembled into a single all-ferric flow battery, at 80 mA / cm². 2 The energy efficiency was 85.8% when tested at current density.
[0056] Example 4 Fabrication of Ni@Ru core-shell structured porous composite electrode (Ni core + Ru shell).
[0057] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0058] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0059] (3) Construction of porous Ru shell: Preparation of Ru-containing 3+ and Zn 2+ The electrolyte, Ru 3+ The concentration is 0.004 mol / L, Zn 2+ The concentration was 0.006 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 20 minutes at -0.7 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a Ru-Zn second alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Ru shell layer.
[0060] (4) Post-treatment: The electrode after the dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60℃ for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Ru-4.
[0061] Modified carbon felt composite electrode CF-Ni@Ru-4: Scanning electron microscopy shows a porous Ni core layer uniformly covering the carbon fiber surface, forming a core-shell structure after Ru shell deposition. Transmission electron microscopy elemental line scanning reveals a clear distribution of Ni cores and Ru shells, increasing the specific surface area to 27.2 μm².2 / g, the electrochemical active area increased to 120.8mF / cm 2 Assembled into a single all-ferric flow battery, at 75 mA / cm². 2 The energy efficiency was 86.5% when tested at current density.
[0062] Example 5 Fabrication of Ni@Bi core-shell structured porous composite electrode (Ni core + Bi shell).
[0063] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0064] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0065] (3) Construction of porous Bi shell: Prepare a mixture containing Bi 3+ and Zn 2+ electrolyte, Bi 3+ The concentration is 0.01 mol / L, Zn 2+ The concentration was 0.01 mol / L, the total concentration was 0.02 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.8 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was rinsed with deionized water and dried at room temperature. Then, the carbon felt coated with a Bi-Zn second alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.1 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Bi shell layer.
[0066] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Bi-5.
[0067] Modified carbon felt composite electrode CF-Ni@Bi-5: Scanning electron microscopy shows a porous Ni core layer uniformly covering the carbon fiber surface, forming a core-shell structure after Bi shell deposition. Transmission electron microscopy elemental line scanning reveals a clear distribution of Ni cores and Bi shells, increasing the specific surface area to 26.5 μm². 2 / g, the electrochemical active area increased to 115.8mF / cm 2 Assembled into a single all-ferric flow battery, at 200 mA / cm². 2 The energy efficiency was 85.2% when tested at current density.
[0068] Example 6 Fabrication of Ni@In core-shell structured porous electrodes (Ni core + In shell).
[0069] (1) Substrate pretreatment: Cut the asphalt-based carbon felt into 10cm×10cm pieces and ultrasonically clean it for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt% HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0070] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0071] (3) Construction of porous In shell: Prepare a mixture containing In 2+ and Zn 2+ electrolyte, In 2+ The concentration is 0.01 mol / L, Zn 2+The concentration was 0.01 mol / L, the total concentration was 0.02 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.9 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the In-Zn second alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 30 minutes, selectively dissolving Zn to form a porous In shell layer.
[0072] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60℃ for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@In-6.
[0073] Modified carbon felt composite electrode CF-Ni@In-6: Scanning electron microscopy shows a porous Ni core layer uniformly covering the carbon fiber surface, forming a core-shell structure after In shell deposition. Transmission electron microscopy elemental line scanning reveals a clear distribution of Ni cores and In shells, increasing the specific surface area to 25.8 μm². 2 / g, the electrochemical active area increased to 112.3mF / cm 2 Assembled into a single all-ferric flow battery, at 50 mA / cm². 2 The energy efficiency was 84.5% when tested at current density.
[0074] Example 7 A Ni@Pt core-shell porous composite electrode (Ni core + Pt shell) was prepared, with a different core layer thickness than in Example 1 (deposition time 20 minutes).
[0075] (1) Substrate pretreatment: Cut the asphalt-based carbon felt into 10cm×10cm pieces and ultrasonically clean it for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt% HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0076] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 20 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution and subjected to a dealloying treatment at 0.1 V vs. SCE potential for 60 minutes using a potentiostatic method to selectively dissolve Zn, forming a porous Ni core layer.
[0077] (3) Construction of porous Pt shell: Preparation of Pt-containing 4+ and Zn 2+ The electrolyte, Pt 4+ The concentration is 0.005 mol / L, Zn 2+ The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.6 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a second Pt-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pt shell.
[0078] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Pt-7.
[0079] Modified carbon felt composite electrode CF-Ni@Pt-7: Scanning electron microscopy reveals a porous Ni core layer uniformly covering the carbon fiber surface, with a core layer thickness of approximately 0.8 μm. After depositing a Pt shell, a core-shell structure is formed. Transmission electron microscopy elemental line scanning shows a clear distribution of the Ni core and Pt shell, increasing the specific surface area to 22.5 m². 2 / g, the electrochemical active area increased to 105.8mF / cm 2 Assembled into a single all-ferric flow battery, at 120 mA / cm². 2 The energy efficiency was 75.8% when tested at current density.
[0080] Example 8 A Co@Pd core-shell porous composite electrode (Co core + Pd shell) was prepared, with a different core layer thickness than in Example 2 (deposition time 20 minutes).
[0081] (1) Substrate pretreatment: Cut the asphalt-based carbon felt into 10cm×10cm pieces and ultrasonically clean it for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt% HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0082] (2) Construction of porous Co core layer: Prepare a Co-containing core layer 2+ and Zn 2+ electrolyte, Co 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 20 minutes at -1.2 V vs. SCE potential at a deposition temperature of 30℃. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Co-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution and subjected to a dealloying treatment at 0.1 V vs. SCE potential for 60 minutes using a potentiostatic method to selectively dissolve Zn, forming a porous Co core layer.
[0083] (3) Construction of porous Pd shell: Prepare a Pd-containing 4+ and Zn 2+ The electrolyte, Pd 4+ The concentration is 0.005 mol / L, Zn 2+ The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Co core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.6 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a second Pd-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pd shell.
[0084] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Co@Pd-8.
[0085] Modified carbon felt composite electrode CF-Co@Pd-8: Scanning electron microscopy reveals a porous Co core layer uniformly covering the carbon fiber surface, with a core layer thickness of approximately 0.8 μm. After depositing a Pd shell, a core-shell structure is formed. Transmission electron microscopy elemental line scanning shows a clear distribution of the Co core and Pd shell, increasing the specific surface area to 18.9 μm. 2 / g, the electrochemical active area increased to 117.4mF / cm 2 Assembled into a single all-ferric flow battery, at 100 mA / cm². 2 The energy efficiency was 77.9% when tested at current density.
[0086] Example 9 A Ni@Pt core-shell porous composite electrode (Ni core + Pt shell) was prepared, with a different shell thickness than in Example 1 (deposition time 8 minutes).
[0087] (1) Substrate pretreatment: Cut the asphalt-based carbon felt into 10cm×10cm pieces and ultrasonically clean it for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt% HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0088] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0089] (3) Construction of porous Pt shell: Preparation of Pt-containing 4+ and Zn 2+ The electrolyte, Pt 4+ The concentration is 0.005 mol / L, Zn 2+The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 8 minutes at -0.6 V vs. SCE potential at a deposition temperature of 30 °C. After deposition, the carbon felt was rinsed with deionized water and dried at room temperature. Then, the carbon felt coated with a second Pt-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pt shell.
[0090] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Pt-9.
[0091] Modified carbon felt composite electrode CF-Ni@Pt-9: Scanning electron microscopy shows a porous Ni core layer uniformly covering the carbon fiber surface, with a thin Pt shell of approximately 0.15 μm. Transmission electron microscopy elemental line scanning reveals a clear distribution of the Ni core and Pt shell, increasing the specific surface area to 24.5 m². 2 / g, the electrochemical active area increased to 108.5mF / cm 2 Assembled into a single zinc-bromine flow battery, at 80 mA / cm². 2 The energy efficiency was 81.5% when tested at current density.
[0092] Example 10 A Ni@Pt core-shell porous composite electrode (Ni core + Pt shell) was prepared, with a different shell thickness than in Example 1 (deposition time 25 minutes).
[0093] (1) Substrate pretreatment: Cut the asphalt-based carbon felt into 10cm×10cm pieces and ultrasonically clean it for 15 minutes each in acetone, ethanol and deionized water. Then soak it in 30wt% HNO3 solution at 80℃ for 2 hours, rinse it repeatedly with deionized water until neutral, and dry it in a vacuum drying oven at 80℃ for 6 hours for later use.
[0094] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ and Zn 2+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Zn 2+The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.2 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.1 V vs. SCE potential for 60 minutes, selectively dissolving Zn to form a porous Ni core layer.
[0095] (3) Construction of porous Pt shell: Preparation of Pt-containing 4+ and Zn 2+ The electrolyte, Pt 4+ The concentration is 0.005 mol / L, Zn 2+ The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed at -0.6 V vs. SCE potential for 25 minutes at a deposition temperature of 30 °C. After deposition, the carbon felt was rinsed with deionized water and dried at room temperature. Then, the carbon felt coated with a second Pt-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a potentiostatic method was used to perform dealloying treatment at 0.2 V vs. SCE potential for 30 minutes, selectively dissolving Zn to form a porous Pt shell.
[0096] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed repeatedly with deionized water 3 times and dried in a vacuum drying oven at 60℃ for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Pt-10.
[0097] Modified carbon felt composite electrode CF-Ni@Pt-10: Scanning electron microscopy shows a porous Ni core layer uniformly covering the carbon fiber surface, with a relatively thick Pt shell of approximately 0.8 μm. Transmission electron microscopy elemental line scanning reveals a clear distribution of the Ni core and Pt shell, increasing the specific surface area to 29.5 m². 2 / g, the electrochemical active area increased to 128.5mF / cm². 2 Assembled into a single zinc-bromine flow battery, at 120 mA / cm². 2 The energy efficiency was 87.3% when tested at current density.
[0098] Example 11 A Ni@Pt core-shell porous composite electrode (Ni core + Pt shell) was prepared, which differed from the core layer structure of Example 1 (Al was used as a sacrificial component).
[0099] (1) Substrate pretreatment: The polyacrylonitrile carbon felt was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 15 minutes each. Then it was soaked in 30wt% HNO3 solution at 80℃ for 2 hours, rinsed repeatedly with deionized water until neutral, and dried in a vacuum drying oven at 80℃ for 6 hours for later use.
[0100] (2) Construction of porous Ni core layer: Preparation of Ni-containing 2+ And Al 3+ electrolyte, Ni 2+ The concentration is 0.1 mol / L, Al 3+ The concentration was 0.1 mol / L, the total concentration was 0.2 mol / L, and 0.1 mol / L sodium citrate was added as a complexing agent. Using the pretreated carbon felt as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode, deposition was performed for 30 minutes at -1.3 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with the first Ni-Al alloy layer was placed in a 0.5 mol / L HCl solution and subjected to a dealloying treatment at 0.1 V vs. SCE potential for 60 minutes using a potentiostatic method to selectively dissolve Al and form a porous Ni core layer.
[0101] (3) Construction of porous Pt shell: Preparation of Pt-containing 4+ and Zn 2+ The electrolyte, Pt 4+ The concentration is 0.005 mol / L, Zn 2+ The concentration was 0.005 mol / L, the total concentration was 0.01 mol / L, and 0.05 mol / L sodium citrate was added as a complexing agent. A carbon felt coated with a porous Ni core layer was used as the working electrode, and deposition was performed for 15 minutes at -0.6 V vs. SCE potential and at a deposition temperature of 30 °C. After deposition, the carbon felt was removed, rinsed with deionized water, and dried at room temperature. Then, the carbon felt coated with a second Pt-Zn alloy layer was placed in a 0.5 mol / L H₂SO₄ solution, and a dealloying treatment was performed for 30 minutes at 0.2 V vs. SCE potential using a potentiostatic method to selectively dissolve Zn and form a porous Pt shell.
[0102] (4) Post-treatment: The electrode after the second dealloying treatment was rinsed three times with deionized water and dried in a vacuum drying oven at 60°C for 6 hours to obtain the modified carbon felt composite electrode CF-Ni@Pt-11.
[0103] Modified carbon felt composite electrode CF-Ni@Pt-11: Scanning electron microscopy reveals a porous Ni core layer uniformly covering the carbon fiber surface, forming a core-shell structure after Pt shell deposition. Transmission electron microscopy elemental line scanning shows a clear distribution of the Ni core and Pt shell, increasing the specific surface area to 26.5 μm².2 / g, the electrochemical active area increased to 118.5mF / cm 2 Assembled into a single zinc-bromine flow battery, at 70 mA / cm². 2 The energy efficiency was 84.2% when tested at current density.
[0104] The results of the examples demonstrate that the stepwise electrochemical dealloying method of this invention can successfully construct a core-shell porous catalyst layer with a "conductive core and catalytically active shell" on the surface of a carbon felt electrode through a simple and controllable process. The composition and synergistic catalytic performance of the core-shell structure can be tuned by selecting different core metals (Ni, Co, Cu) and shell metals (Pt, Pd, Ir, Ru, Bi, In, Sb); the thickness of the core layer can be controlled by adjusting the first deposition time; and the thickness of the shell layer can be controlled by adjusting the second deposition time. The prepared core-shell porous electrode exhibits a synergistic effect between the high conductivity of the core layer and the high catalytic activity of the shell layer, resulting in an increased specific surface area. By adjusting the alloy composition, deposition parameters, and dealloying conditions, the pore size, thickness, and elemental composition of the core and shell layers can be precisely controlled. This electrode, through its inherent core-shell structure design, effectively coordinates the synergistic effect of the core-shell interface and meets the multiple requirements of flow battery electrodes for high conductivity (core layer), high catalytic activity (shell layer), and high specific surface area, providing a key electrode material solution for the development of next-generation high-performance, high-power-density flow batteries.
Claims
1. A method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying, characterized in that, Includes the following: The carbon felt substrate is first acid-treated to introduce oxygen-containing functional groups, and then a first alloy layer is deposited on the surface. The first alloy layer has a first catalytically active component and a first sacrificial component. Then, a first dealloying process is performed to remove the first sacrificial component and form a porous metal core layer with conductivity. A second alloy layer is then deposited on the porous metal core layer. The second alloy layer has a second catalytically active component and a second sacrificial component. Then, a second dealloying process is performed to remove the second sacrificial component and form a porous shell layer with catalytic activity. Thus, a core-shell porous catalyst layer is formed in situ on the surface of the carbon felt substrate, resulting in a composite electrode with a core-shell porous catalyst layer loaded on its surface.
2. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The carbon felt substrate includes polyacrylonitrile-based carbon felt, pitch-based graphite felt, adhesive-based carbon felt, or carbon paper. The acid treatment includes the following steps: the carbon felt substrate is ultrasonically degreased in acetone, ethanol, and deionized water for 10-30 minutes in sequence, then soaked in 5wt%-30wt% HNO3 or H2SO4 solution at 60℃-90℃ for 1-6 hours to introduce oxygen-containing functional groups, washed with deionized water until neutral, and then dried at 60℃-100℃ for 6-12 hours.
3. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The first catalytic active component is selected from one or more of Ni, Co, and Cu; the first sacrificial component is selected from one or more of Zn, Al, and Mg; in the first alloy layer, the total atomic percentage of the first catalytic active component is 30% to 80%, and the total atomic percentage of the first sacrificial component is 20% to 70%.
4. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The deposited first alloy layer includes the following: An electrochemical deposition method was used to deposit a first alloy layer on the surface of a carbon felt substrate. The electrolyte for electrochemical deposition was a metal ion salt solution containing a first catalytically active component and a first sacrificial component. The total concentration of metal ions was 0.01 mol / L to 0.5 mol / L, the deposition potential was -1.5 V to -0.5 V, the deposition time was 5 to 60 minutes, and the deposition temperature was 25℃ to 50℃.
5. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The first dealloying process includes the following: The first sacrificial component was selectively dissolved in an acidic medium using an electrochemical dealloying method. The acidic medium was a 0.1 mol / L to 2.0 mol / L solution of H2SO4, HCl, or HNO3. The dealloying potential was -0.2 V to 0.5 V, and the processing time was 10 to 120 minutes.
6. The method for preparing a supported core-shell structured catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The second catalytic active component is selected from one or more of Pt, Pd, Ir, Ru, Bi, In, and Sb; the second sacrificial component is selected from one or more of Zn, Al, and Mg; in the second alloy layer, the total atomic percentage of the second catalytic active component is 30% to 80%, and the total atomic percentage of the second sacrificial component is 20% to 70%.
7. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The deposited second alloy layer includes the following: A second alloy layer was deposited on a porous metal core layer using an electrochemical deposition method. The electrolyte for electrochemical deposition contained a metal ion salt solution of a second catalytically active component and a second sacrificial component. The total metal ion concentration was 0.001 mol / L to 0.1 mol / L, the deposition potential was -1.0 V to -0.4 V vs. SCE, the deposition time was 5 to 30 minutes, and the deposition temperature was 25℃ to 40℃.
8. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The second dealloying process includes the following: The second sacrificial component was selectively dissolved in an acidic medium using an electrochemical dealloying method. The acidic medium was a 0.1 mol / L to 2.0 mol / L solution of H2SO4, HCl, or HNO3. The dealloying potential was -0.2 V to 0.5 V vs. SCE, and the processing time was 10 to 90 minutes.
9. The method for preparing a supported core-shell catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, During the first and second dealloying processes, inert gas was introduced for stirring or ultrasonic assistance, with a gas flow rate of 10 mL / min to 100 mL / min and an ultrasonic power of 50 W to 300 W. After the second dealloying treatment, the electrode is rinsed 3 to 5 times with deionized water or ethanol and dried at 60℃ to 100℃ for 6 to 12 hours to obtain a composite electrode with a core-shell structured porous catalyst layer on its surface.
10. The composite electrode obtained by the preparation method of the supported core-shell structure catalyst composite electrode based on electrochemical dealloying according to claim 1, characterized in that, The composite electrode is used as a flow battery electrode and is suitable for all-vanadium redox flow batteries, iron-chromium redox flow batteries, all-iron redox flow batteries, and zinc-based redox flow batteries. The catalytically active component of the porous metal core layer contains one or more of Ni, Co, and Cu, and the catalytically active component of the porous shell layer contains one or more of Pt, Pd, Ir, Ru, Bi, In, and Sb. The porous metal core layer has a pore size of 10 nm to 100 nm, a porosity of 30% to 70%, and a thickness of 0.5 μm to 5 μm; the porous shell layer has a pore size of 5 nm to 50 nm, a porosity of 30% to 60%, and a thickness of 0.1 μm to 2 μm; the specific surface area of the core-shell structured porous catalyst layer is 15 m². 2 / g~60m 2 / g, with an electrochemical active area of 80mF / cm² 2 ~150mF / cm 2 .